A profile of social isolation and the influence of demographics in older persons living in residential care, Durban, South Africa - Mary Ann Jarvis; Suvira Ramlall; Jennifer Chipps (Elsevier, 2021)
Introduction: Residential care settings have shown high social isolation rates with incumbent risks necessitating measurement to formulate health promotion policies. Objective: To measure social isolation levels in older persons living in a lower socio-economic residential care setting in South Africa. Method: A cross sectional survey with older persons from four inner city residential care facilities. A researcher-administered questionnaire was developed based on the Working Paper No.66, Oxford Poverty and Human Development Initiative. Data were analysed to describe social isolation and assess the influence of demographics. Results: The response rate was 72.14% (n = 277) and representative of the residential care population for age and gender. Nearly half of the respondents (47.3%) met criteria for social isolation in terms of social network support and density and almost 20% for perceived isolation through decreased levels of friendship. Conclusion: Although residential care does not prevent social isolation, the residents in the setting may provide a buffering in the provision of some social support.